Environmental literacy profile of 7th grade junior high school students in science learning on global warming subject. (March 2020) - Maulaa, I; Hamidah, I; Permanasari, A
Abstract: This paper examined environmental literacy which has become a global issue in the world. This study aimed at analysing the environmental literacy profile of junior high school students in one of junior high schools in Bandung, West Java Indonesia. The method used was pre-experimental method employing scientific descriptions that were explored descriptively. The population and sample were 96 students in the 7 th -grade of junior high school. Environmental literacy was measured by 30 multiple choice questions covering aspects of knowledge, environmental affective, cognitive skills, and behaviour. An environmental literacy test was developed adopting the Middle Schools Environmental Survey/Instrument (MSELS/I) test questions used by NELA. The results indicated that the environmental literacy of the students was classified as the medium category. The scores obtained by students for each aspect were not significantly different. Knowledge aspects, affective environment, cognitive skills, and behaviour score of 53.28, 47, 52, 56.64 and 49.17, respectively. Based on the achievement level of each group of students, environmental literacy obtained for the high, medium and low categories were 11%, 57%, and 32%, respectively. Based on these results, it can be concluded that teacher efforts to make learning better, more innovative, and oriented towards environmental literacy were highly required.